“Tecendo os fios da política socioeducativa no Brasil”: uma avaliação política do sistema nacional de atendimento socioeducativo-SINASE - SOUSA, Mara Alves de (2023)
This work focuses on the National System of Socio-Educational Assistance - Sinase and proposes as its central objective: to develop a political evaluation, focusing on the conception and design of Sinase, considering the political, economic, social and cultural dimensions that conditioned the process of its formulation, as well as the central principles that underlie this policy. Throughout this research, the socio- historical construction of the child protection policy in Brazil is contextualized, highlighting a look at childhood and adolescence and the markers of the social issue from the context of the formation of Brazilian society. The aim is, therefore, to demarcate the policies of assistance to adolescents in conflict with the law in Brazil from the 1930s onwards, a period marked by the consecration of the doctrine of the irregular situation. The trajectory of the construction of the paradigm of Integral Protection in the Brazilian public agenda, from the 80's, is situated, pointing out some (dis)encounters with regard to the policy of socio-educational assistance. It presents, with emphasis, Sinase as a Public Policy, highlighting its trajectory and emergence in the public agenda and its formulation. The research is based on the methodology of political evaluation of politics, conducted by the theoretical-methodological aspect of historical-dialectical materialism, considering Sinase as a complex of multiple determinations and part of the dialectic of the societal movement. A bibliographic and documental qualitative research approach is used, as this allows for reflection on the complexity of the issues under analysis. As the main results of the study, some disagreements were identified regarding the principles of Sinase, which are based on overcoming previous models and affirming socio-education based on human rights, however, the analysis indicated that this process has been expressed through continuities and discontinuities (in permanent dispute) in Brazilian society, accompanying the inflections present in the different socio-political conjunctures and in dealing with the infraction issue.